Prenatal exposure to phthalates and preschool children’s intellectual scores: Effect modification by child sex - Carly V. Goodman; Christine Till; Sietske Berghuis; Joseph M. Braun; Gina Muckle; Aimin Chen; Youssef Oulhote; Bruce Lanphear; Jillian Ashley-Martin; Tye E. Arbuckle (Environment International)
Background: Some epidemiological studies suggest that phthalates adversely affect children’s neurodevelopment, but results are inconsistent and often only consider individual chemicals. Objectives: We examined associations between gestational phthalate metabolites and intelligence at ages 3–4 and investigated effect modification by child sex. Methods: We analyzed data from 511 mother–child pairs enrolled in the Maternal-Infant Research on Environmental Chemicals study. We measured specific gravity-standardized urinary concentrations of 20 phthalate metabolites (from nine parent compounds) in trimesters 1 and 2 and computed the average. We used linear regression models (log2-transformed), adjusting for covariates, to examine single-chemical associations with Full-Scale (FSIQ), Performance (PIQ), and Verbal IQ (VIQ) measured by the Weschler Preschool and Primary Scale of Intelligence-III. We estimated mixture effects using weighted quantile sum (WQS) regression. Results: Detection frequencies of the metabolites ranged from 42 to 99%. In single-chemical analyses, the sum of di-isodecyl phthalate metabolites (ΣDiDPm) was associated with decreased FSIQ (−0.5, 95%CI: −2.1, −0.0) and PIQ (−0.6, 95%CI: −1.2, −0.0). Monomethyl phthalate (MMP) was associated with increased FSIQ (1.7, 95%CI: 0.4, 3.1), PIQ (1.7, 95%CI: 0.2, 3.1) and VIQ; (1.6, 95%CI: 0.3, 2.8). Monobenzyl phthalate (MBzP) was positively associated with PIQ (0.9, 95%CI: 0.0, 1.9). Associations between ΣDiDPm and VIQ and MMP and PIQ differed by child sex (negative for boys and positive for girls, respectively). WQS analyses were not statistically significant. Conclusions: Findings from this pan-Canadian cohort provide some evidence that gestational ΣDiDPm is adversely associated with child cognition, with sex-specific vulnerabilities. The positive associations with MMP and MBzP warrant further research.